Wiskott-Aldrich syndrome protein regulates autophagy and inflammasome activity in innate immune cells. Issue 1 (December 2017) - Lee, Pamela; Lobato-Márquez, Damián; Pramanik, Nayani; Sirianni, Andrea; Daza-Cajigal, Vanessa; Rivers, Elizabeth; Cavazza, Alessia; Bouma, Gerben; Moulding, Dale; Hultenby, Kjell; Westerberg, Lisa; Hollinshead, Michael; et al.
Abstract Dysregulation of autophagy and inflammasome activity contributes to the development of auto-inflammatory diseases. Emerging evidence highlights the importance of the actin cytoskeleton in modulating inflammatory responses. Here we show that deficiency of Wiskott–Aldrich syndrome protein (WASp), which signals to the actin cytoskeleton, modulates autophagy and inflammasome function. In a model of sterile inflammation utilizing TLR4 ligation followed by ATP or nigericin treatment, inflammasome activation is enhanced in monocytes from WAS patients and in WAS-knockout mouse dendritic cells. In ex vivo models of enteropathogenicEscherichia coli andShigella flexneri infection, WASp deficiency causes defective bacterial clearance, excessive inflammasome activation and host cell death that are associated with dysregulated septin cage-like formation, impaired autophagic p62/LC3 recruitment and defective formation of canonical autophagosomes. Taken together, we propose that dysregulation of autophagy and inflammasome activities contribute to the autoinflammatory manifestations of WAS, thereby identifying potential targets for therapeutic intervention. Wiskott-Aldrich syndrome protein (WASp) is essential for controlling the cytoskeleton, but its function in innate immunity is unclear. Here the authors show that WASp deficiency is associated with dysregulated septin cage formation, excessive inflammasome activation, elevated immune cell death and reduced bacterial clearance.